Horn presence determines social rank in Dorper rams - Calderon-Leyva, Guadalupe; Sifuentes-Lamont, Pablo Ivan; Contreras-Villarreal, Viridiana; Angel-Garcia, Oscar; Moreno-Avalos, Silvestre; Veliz-Deras, Francisco Gerardo; Alvarado Espino, Alan Sebastian (Ecosistemas y Recursos Agropecuarios, 2024)
The aim was to determine if the presence of horns on rams defines whether they are high-ranking or low-ranking. Dorper rams (n = 20) were evaluated to determine their social rank (SR), either high (HSR) or low (LSR), under intensive management conditions. Upon SR classification, the morphometric variables horns presence (HP) or absence (HA) and distance between them, the height at the withers, body length, thoracic perimeter, and scrotal circumference, male odor, body weight, and body condition score were registered. Afterward, semen evaluations were performed, recording the ejaculated volume, sperm concentration, and mass motility. There were no differences (p > 0.05) for the morphometric variables between the groups. However, HP as well as semen quality were higher (p < 0.05) in HSR males. The presence of horns in the rams determined their social rank and the dominant males showed better semen quality than the subordinate males.